Research in social movements, conflicts and change. Vol. 26 - Coy, Patrick G. (Amsterdam ; Oxford : Elsevier JAI, 2005)
Over the past decade social movement scholarship has reflected the robust nature of many of the movements themselves. Innovative lines of inquiry and new theoretical frameworks have opened up to reinvigorate the field. This volume reflects this welcome trend. The volume opens with two papers analyzing tactical and strategic innovations in movement organizing. One establishes that the woman's suffrage movement relied on both outsider (contentious) politics and insider (institutionalized) politics, while the other addresses the promises and pitfalls of transitional social movements that organize through the Internet. Another area of recently invigorated research is on the repression of social movements, and this volume includes two such papers. Mobilization concerns associated with political protest in high-risk settings are empirically addressed in one paper while the other contributes to the policing of protest literature by critically analyzing the costs to movements of arrests. Using newspaper coverage of social movements for events data has risen lately thanks in part to the Internet and new software. We include two papers that reflect this trend and which address emerging methodological concerns associated with it. Perhaps the most fertile area of social movement research examines the increasingly complex and busy intersection of collective identity issues with social movement membership and mobilization. Thus we close this volume with three papers representing this new theorizing. "Research in Social Movements, Conflicts and Change" continues it distinguished tradition of reflecting recent trends in social movement scholarship while also contributing to new theorizing.
Introduction / Patrick G. Coy -- Specialists and generalists: learning strategies in the woman suffrage movement, 1866-1918 / Brayden G. King, Marie Cornwall -- Transnational activism in the Americas: the Internet and innovations in the repertoire of contention / Jeffrey M. Ayres -- Multi-sectoral coalitions and popular movement participation / Paul D. Almeida -- "You can beat the rap, but you can't beat the ride:" bringing arrests back into research on repression / Jennifer Earl -- Addressing the selection bias in media coverage of strikes: a comparison of mainstream and specialty print media / Andrew W. Martin -- Wilderness or working forest? British Columbia forest policy debate in the Vancouver Sun, 1991-2003 / Mark C.J. Stoddart -- We don't agree: collective identity justification work in social movement organizations / Belinda Robnett -- Construction of relationship frames in the aboriginal rights support movement: the articulation of solidarity with the Lubicon Cree of northern Canada / Neil Funk-Unrau -- Possibility of personal empowerment in dispute resolution: Habermas, Foucault and community mediation / Jordi Agusti-Pamareda.
Description based on print version record.
Keywords: Social movements; Social conflict; Social psychology; Social issues & processes; Social Science -- Sociology -- General